The Development of Internal Supervision Guidelines using the Professional Learning Community Concept for Schools in Surin Secondary Educational Service Area - Maithong, Adisak; Namwan, Tharinthorn (CRMA Journal of Humanities and Social Sciences, 2024)
The objectives of the research were to: 1) Study the current and desirable states, as well as the priority needs of the Internal Supervision Guidelines, using the Professional Learning Community (PLC) Concept; and 2) Develop the Internal Supervision Guidelines using the PLC Concept for Schools in Surin Secondary Educational Service Area. The study was divided into 2 phases. The sample population was 454 administrators and teachers, which was derived by stratified random sampling. The research tools were: 1) A set of questionnaires; 2) An interview form; and 3) A guidelines assessment form. The data were analyzed via the calculations of frequency, percentage, mean, and standard deviation. The results of this study were: 1) The current state of the Internal Supervision Guidelines using the PLC Concept for Schools overall was at a high level and the desirable state of the Internal Supervision Guidelines using the PLC Concept for Schools overall was at the highest level. The Priority Needs Index of the Internal Supervision Guidelines as ordered from the highest to lowest needs were as follows: the study of current problems and needs of internal supervision, planning of internal supervision, implementation of internal supervision, the reflection, report, and dissemination of internal supervision results, and evaluation, monitoring, and improvement of internal supervision work; and 2) The Internal Supervision Guidelines using the PLC Concept for Schools consists of 30 guidelines. The results of the suitability and feasibility assessment of the Internal Supervision Guidelines found that the guidelines were appropriate at the highest level and overall feasibility was at the highest level.